2003
DOI: 10.1016/s0092-8674(03)00465-3
|View full text |Cite
|
Sign up to set email alerts
|

Human CLASP1 Is an Outer Kinetochore Component that Regulates Spindle Microtubule Dynamics

Abstract: One of the most intriguing aspects of mitosis is the ability of kinetochores to hold onto plus ends of microtubules that are actively gaining or losing tubulin subunits. Here, we show that CLASP1, a microtubule-associated protein, localizes preferentially near the plus ends of growing spindle microtubules and is also a component of a kinetochore region that we term the outer corona. A truncated form of CLASP1 lacking the kinetochore binding domain behaves as a dominant negative, leading to the formation of rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
245
2
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 202 publications
(267 citation statements)
references
References 64 publications
19
245
2
1
Order By: Relevance
“…In agreement with previous studies (Maiato et al, 2003(Maiato et al, , 2005Rogers et al, 2004), we found that the flux rate was significantly decreased after RNAi treatments to deplete either Mast or KLP10A (Figure 1, A and B; Supplementary Movie 2). The extent of flux rate decrease after Mast or KLP10A RNAi (decreased 74 or 65%, respectively, relative to control rate) was comparable to the decrease measured in cells treated with low concentrations of colchicine or taxol to suppress microtubule dynamics (Supplementary Figure 2).…”
Section: Regulation Of Poleward Flux By Mast and Klp10asupporting
confidence: 92%
“…In agreement with previous studies (Maiato et al, 2003(Maiato et al, , 2005Rogers et al, 2004), we found that the flux rate was significantly decreased after RNAi treatments to deplete either Mast or KLP10A (Figure 1, A and B; Supplementary Movie 2). The extent of flux rate decrease after Mast or KLP10A RNAi (decreased 74 or 65%, respectively, relative to control rate) was comparable to the decrease measured in cells treated with low concentrations of colchicine or taxol to suppress microtubule dynamics (Supplementary Figure 2).…”
Section: Regulation Of Poleward Flux By Mast and Klp10asupporting
confidence: 92%
“…It has been shown that human CLASP1 is an outer kinetochore component that regulates spindle microtubule dynamics (21). Recent studies show that improper microtubule-chromosome attachment (merotely) is a cause of chromosome missegregation in unstable cells and that increasing chromosome mis-segregation rates by elevating merotely during consecutive mitoses generates chromosome instability in otherwise stable, near-diploid cells (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…Yet, little is known regarding the molecular machinery that governs the integrated coordination of various cytoskeletal components. Evidence suggests that the microtubule (MT) plus-end tracking protein CLASP [cytoplasmic linker protein (CLIP)-associated protein], which has been implicated in mitotic spindle formation (Inoue et al 2000(Inoue et al , 2004 and in linking MT ends to other cell structures such as the cell cortex and kinetochore (Akhmanova et al 2001;Maiato et al 2003;Mimori-Kiyosue et al 2005;Reis et al 2009), may play a pivotal role in the overall coordination of cytoskeletal networks. Not only does it affect MT dynamics, but CLASP may function as an actin-MT crosslinker as well, as it possesses actin-binding activity (Tsvetkov et al 2007) and CLASP-bound microtubules appear to track along F-actin bundles in growth cones (Lee et al 2004).…”
Section: Oordination Of Cytoskeletal Dynamics Is Anmentioning
confidence: 99%